2010
DOI: 10.1161/atvbaha.110.209692
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Analysis on the Differentiation of Bone Marrow-Derived Progenitor Cells Into Smooth Muscle Cells During Neointima Formation

Abstract: Objective-Bone marrow-derived progenitor cells have been implicated to contribute to neointima formation, but the time course and extent of their accumulation and differentiation into vascular cells and, most importantly, the long-term contribution of bone marrow-derived progenitor cells to the vascular lesion remain undefined. Methods and Results-Wire-induced injury of the femoral artery was performed on chimeric C57BL/6 mice transplanted with bone marrow from transgenic mice expressing enhanced green fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 23 publications
6
72
0
Order By: Relevance
“…31 These findings have remained controversial, in part because of the disputed ability of BM-derived cells to give rise to SMCs and because recent publications have directly contradicted the earlier data. 32,33 Recently, Iwata et al, working in 3 separate models of IH including TA, reported significant numbers of recipient ␣-SMA ϩ SM22␣ ϩ cells in the neointima, but these also expressed CD115, CD11b, F4/80, and Ly-6C, markers of the monocyte/macrophage lineage rather than established markers of differentiated SMCs such as smooth muscle myosin heavy chain or calponin. 8 The authors concluded that although BM-derived ␣-SMA ϩ cells were involved in vascular remodeling, they were myeloid cells and not true SMC progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…31 These findings have remained controversial, in part because of the disputed ability of BM-derived cells to give rise to SMCs and because recent publications have directly contradicted the earlier data. 32,33 Recently, Iwata et al, working in 3 separate models of IH including TA, reported significant numbers of recipient ␣-SMA ϩ SM22␣ ϩ cells in the neointima, but these also expressed CD115, CD11b, F4/80, and Ly-6C, markers of the monocyte/macrophage lineage rather than established markers of differentiated SMCs such as smooth muscle myosin heavy chain or calponin. 8 The authors concluded that although BM-derived ␣-SMA ϩ cells were involved in vascular remodeling, they were myeloid cells and not true SMC progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IMD-0354 inhibited in vitro mouse-derived VSMC proliferation induced by PDGF-BB, TNF-α, and IL-1β. Previous reports have suggested that there are fewer inflammatory cells in the neointima, 32) and that bone marrow-derived cells in the neointima lesion mainly differentiate into macrophage lineages. 33) Thus, the main role of these cells in the development of a neointimal lesion is to initiate inflammation and induce VSMC proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…As was discussed in Chapter II, when we looked at mice which were slightly older, those around 17-19 weeks of age and compared them to our [10][11][12] week old mice, we saw a significant reduction in the eYFP+ contribution to the neointima in the PDGFRB SMC WT/WT mice. We then found through continuous BrdU infusion that PDGFRB SMC WT/WT mice 10-12 weeks of age had a higher growth fraction than those PDGFRB SMC WT/WT mice 17-19 weeks of age.…”
Section: Age Related Studiesmentioning
confidence: 83%
“…Further, multiple genes originally thought to be SMC-specific have now been identified as being expressed in alternative cell types including bone marrow cells 11,[20][21][22][23] , adventitial cells [24][25][26] , endothelial cells 27 , and more 28,29 , with the only gene currently thought to be specific to SMCs (and pericytes, a perivascular cell similar to SMCs in the microvasculature) being Myh11 17 . Indeed this ambiguity led to several papers 23,30,31 suggesting additional de novo sources of SMCs being derived from cells other than SMCs.…”
Section: Phenotypic Switchingmentioning
confidence: 99%
See 1 more Smart Citation